Systematic repression of transcription factors reveals limited patterns of gene expression changes in ES cells - Nishiyama, Akira; Sharov, Alexei A.; Piao, Yulan; Amano, Misa; Amano, Tomokazu; Hoang, Hien G.; Binder, Bernard Y.; Tapnio, Richard; Bassey, Uwem; Malinou, Justin N.; Correa-Cerro, Lina S.; Yu, Hong; et al. (Scientific reports, 2013)
Networks of transcription factors (TFs) are thought to determine and maintain the identity of cells. Here we systematically repressed each of 100 TFs with shRNA and carried out global gene expression profiling in mouse embryonic stem (ES) cells. Unexpectedly, only the repression of a handful of TFs significantly affected transcriptomes, which changed in two directions/trajectories: one trajectory by the repression of either Pou5f1 or Sox2 ; the other trajectory by the repression of either Esrrb , Sall4 , Nanog , or Tcfap4 . The data suggest that the trajectories of gene expression change are already preconfigured by the gene regulatory network and roughly correspond to extraembryonic and embryonic fates of cell differentiation, respectively. These data also indicate the robustness of the pluripotency gene network, as the transient repression of most TFs did not alter the transcriptomes.